Evolusi Dental Komposit Estetis - Ridhayani Hatta; Mohamad Arif Budiman Putra Pratama (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
Dental composite defined as a combination of two or more different materials with superior properties possessed, thus resulting in better properties than the original material, which hardened through the polymerization process. This restorative material is widely used because it has a higher aesthetic value compared to other dental filling materials. The evolution of composite resins in dentistry has occurred since they were first introduced as dental restorative materials, until now, the development of materials continues to increase significantly, especially in their aesthetic value. A good aesthetics material will greatly affect the results of the treatment in clinical applications.